2022
DOI: 10.1177/14604582221077049
|View full text |Cite
|
Sign up to set email alerts
|

Moving toward AI-assisted decision-making: Observation on clinicians’ management of multimedia patient information in synchronous and asynchronous telehealth contexts

Abstract: Background. Artificial intelligence (AI) intends to support clinicians’ patient diagnosis decisions by processing and identifying insights from multimedia patient information. Objective. We explored clinicians’ current decision-making patterns using multimedia patient information (MPI) provided by AI algorithms and identified areas where AI can support clinicians in diagnostic decision-making. Design. We recruited 87 advanced practice nursing (APN) students who had experience making diagnostic decisions using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Compared with traditional face-to-face clinical settings, studies reported that clinicians found telehealth convenient, fast (Hah & Goldin, 2022) and engaging (Barken et al, 2017). However, the inconvenience of not being able to perform physical assessment led clinicians to ask for more information and a detailed medical history via the mode of telehealth (Hah & Goldin, 2022), pay more attention to the tone of the voice (Haimi et al, 2018;Wouters et al, 2020) and check parents' health literacy if children were patients (Haimi et al, 2018(Haimi et al, , 2020. Clinicians were also concerned that a lack of accurate risk assessment could lead to misdiagnosis.…”
Section: Benefits and Risksmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with traditional face-to-face clinical settings, studies reported that clinicians found telehealth convenient, fast (Hah & Goldin, 2022) and engaging (Barken et al, 2017). However, the inconvenience of not being able to perform physical assessment led clinicians to ask for more information and a detailed medical history via the mode of telehealth (Hah & Goldin, 2022), pay more attention to the tone of the voice (Haimi et al, 2018;Wouters et al, 2020) and check parents' health literacy if children were patients (Haimi et al, 2018(Haimi et al, , 2020. Clinicians were also concerned that a lack of accurate risk assessment could lead to misdiagnosis.…”
Section: Benefits and Risksmentioning
confidence: 99%
“…Two studies explored video consultation (Hah & Goldin, 2022;Haimi et al, 2018). Hah and Goldin (2022) found that in asynchronous TA B L E 2 Inclusion and exclusion criteria.…”
Section: Processing Multi-media Patient Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…If you are interested in this, you should read the paper. And last but not least, we have a paper from Hah and Goldin [26] in our selection. It is on AI-assisted decision-making in healthcare.…”
Section: Insights Into the Candidate Papers And Best Papersmentioning
confidence: 99%
“…Otro componente, que se convierte en una oportunidad, está relacionado con el ajuste de los tratamientos personalizados a partir del análisis que la IA permite realizar de los datos de un paciente: historial médico, resultados de pruebas y exámenes, entre otros, para predecir posibles respuestas a diferentes tratamientos. En esta misma perspectiva, el fortalecimiento de la telemedicina puede ser una estrategia de atención especializada al alcance de poblaciones vulnerables y distantes de los centros especializados de diagnóstico (10) .…”
Section: Oportunidades Que Emergen: El Reto De La Colaboraciónunclassified